2011
DOI: 10.1242/jcs.083287
|View full text |Cite
|
Sign up to set email alerts
|

A lipid-droplet-targeted O-GlcNAcase isoform is a key regulator of the proteasome

Abstract: Summary Protein-O-linked N-Acetyl-b-D-glucosaminidase (O-GlcNAcase, OGA; also known as hexosaminidase C) participates in a nutrientsensing, hexosamine signaling pathway by removing O-linked N-acetylglucosamine (O-GlcNAc) from key target proteins. Perturbations in O-GlcNAc signaling have been linked to Alzheimer's disease, diabetes and cancer. Mammalian O-GlcNAcase exists as two major spliced isoforms differing only by the presence (OGA-L) or absence (OGA-S) of a histone-acetyltransferase domain. Here we demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
78
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 41 publications
(61 reference statements)
7
78
0
2
Order By: Relevance
“…Selective knockdown of OGA-S results in global proteasome inhibition and increased levels of perilipin-2 and -3. These findings suggest that proteasomal modulation links O-GlcNAc signaling to lipid droplet maturation (71).…”
Section: O-glcnacylation Regulates Protein Ubiquitination Via Unknownmentioning
confidence: 77%
See 1 more Smart Citation
“…Selective knockdown of OGA-S results in global proteasome inhibition and increased levels of perilipin-2 and -3. These findings suggest that proteasomal modulation links O-GlcNAc signaling to lipid droplet maturation (71).…”
Section: O-glcnacylation Regulates Protein Ubiquitination Via Unknownmentioning
confidence: 77%
“…The short form of O-GlcNAcase (OGA-S), which lacks the histone acetyltransferase domain, accumulates on the surface of lipid droplets (71). Selective knockdown of OGA-S results in global proteasome inhibition and increased levels of perilipin-2 and -3.…”
Section: O-glcnacylation Regulates Protein Ubiquitination Via Unknownmentioning
confidence: 99%
“…HAS2 is known to be mono-and polyubiquitinated, and although monoubiquitination seems to be involved in enzyme dimerization, polyubiquitination does not seem directly related to proteasomal degradation (13). Recently, it was described that the short OGA isoform promotes the proteasomal degradation of surface lipid droplet proteins (54,55) and therefore could have a role in the regulation of HAS2 degradation. Moreover, very recent literature describes the presence of an OGT in the ER (EOGT) conserved in Drosophila and mice (56,57), which could regulate the HAS2 folding process or its escape from the ER.…”
Section: Discussionmentioning
confidence: 99%
“…The other major O-GlcNAcase isoform has a 14-amino extension that serves to target it to lipid droplets. This O-GlcNAcase isoform is involved in the remodeling of lipid droplet surface proteins by local activation of proteasomes on the lipid droplet surface (38,42). This study suggested a nexus between the regulation of lipid storage and hexosamine signaling through O-GlcNAc cycling (42).…”
mentioning
confidence: 89%